Jesse James and the movies - Boggs, Johnny D. (McFarland & Co., Inc., Publishers, 2011)
"This illustrated filmography analyzes the plots and players of the more than forty motion pictures about the legendary Missouri outlaw Jesse James (1847-1882), from the silent era to the 21st century. Each evaluation compares Hollywood's version of history to the hard facts. A brief biography of the outlaw provides an overview of his life and career"--Provided by the publisher.